What kinds of microaggressions do women experience in the health care setting? Examining typologies, context and intersectional identities - Piccinelli, E. (2020)
Microaggressions are everyday verbal and non-verbal indignities, promoted intentionally or by well-intentioned people towards minority and disadvantaged individuals or groups. Microaggressions are often unconscious, socially normalized and naturalized. This qualitative study intended to examine and understand microaggressions lived by women with different intersectional identities (women of Color, immigrant women, straight women, LGBTQ+ women, functionally diverse women) in the Portuguese healthcare context. Semi-structured interviews were conducted using the Critical Incident Technique. Seventeen self-identified female feminists, activists and/or that were involved with NGOs and organizations actively committed to social causes participated. Content and thematic analysis were used in order to recognize the different microaggressive forms (microinsults, microinvalidations, microassaults) and manifestations (verbal, nonverbal/behavioral, environmental) committed in the healthcare context. The results are discussed in light of diversity training opportunities to raise awareness about subtle forms of discrimination among health care practitioners.